1969
DOI: 10.1073/pnas.64.1.345
|View full text |Cite
|
Sign up to set email alerts
|

SELECTIVE TRANSLATION OF T4 TEMPLATE RNA BY RIBOSOMES FROM T4-INFECTED Escherichia coli

Abstract: Abstract.-The present studies indicate that T4 infection induces an alteration in host ribosomes which restricts the translation of host and other T4-unrelated template RNAs but permits normal translation of T4 RNA. A heat-labile factor has been isolated from T4-infected cell ribosomes which, when combined with normal cell ribosomes, confers upon the latter the property of selective T4 template RNA translation.Recent reports from this laboratory1' 2 and others3 have provided evidence for the coding of transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

1971
1971
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…In this Review, “translation efficiency (TE)” is referred to as the rate of protein production per mRNA [1416]. In other contexts, the same phrase has been defined as the rate of translation elongation, which affects the efficiency with which ribosomes are used [13, 17, 18].…”
Section: Defining Translation Efficiencymentioning
confidence: 99%
“…In this Review, “translation efficiency (TE)” is referred to as the rate of protein production per mRNA [1416]. In other contexts, the same phrase has been defined as the rate of translation elongation, which affects the efficiency with which ribosomes are used [13, 17, 18].…”
Section: Defining Translation Efficiencymentioning
confidence: 99%
“…Comparisons have been based on translation of very different mRNAs under standard conditions and hence are not absolute. The ribosomes, which are likely responsible for the poor compatibilities, could be modified by phages or episomes (Hsu & Weiss, 1969;Dube & Rudland, 1970;Morrison & Malamy, I y I ) , but as the incidence of poor compatibility is high the differences are more likely inherent. Since the genome of RNA-containing coliphage can sometimes be effectively translated by phylogenetically remote systems (Schwartz, Eisenstadt, Brawerman & Zinder, I 965), translational variations may in part reflect random differences among ribosomes.…”
Section: F H O W K S S S a R I M O A N D M J Pinementioning
confidence: 99%
“…Incompatibilities may be conferred by specific modifying factors (Hsu & Weiss, 1969;Dube & Rudland, 1970;Morrison & Malamy, 1971), or they may also normally exist in polypeptide incorporating systems of Bacillus stearothernzophilus (Lodish, 1970) and a psychrophilic pseudomonad (Szer & Brenowitz, I 970). We have also observed that Streptococcus faecium preparations are unable to translate RNA of the Qp phage of E. coli at high or low Mgt2 levels (Sarimo & Pine, 1971 ;and unpublished experiments).…”
Section: Introductionmentioning
confidence: 99%
“…Infection of Escherichia coli by the deoxyribonucleic acid (DNA) phage T4 results in cessation of host ribonucleic acid (RNA) and protein synthesis. Mechanisms proposed to account for this include alterations in the host membrane (6,8), synthesis of a T4-specific factor for initiation of transcription (30), a loss of certain host transfer RNA (tRNA) species (29) with replacement by phage-specific tRNA species (4,28), and a change in the factors required for initiation of messenger translation (5,16,19,20).…”
mentioning
confidence: 99%
“…Several investigators have reported that ribosomes from cultures harvested 12 or 13 min after infection by T4 are inhibited in their ability to translate or bind f2 RNA; experiments mixing components from uninfected and T4-infected cells showed that the origin of the initiation factors determined the ability to recognize f2 RNA (5,16).…”
mentioning
confidence: 99%